Analisis Pengaruh Sikap, Norma Subyektif, Dan Kontrol Keperilakuan Terhadap Perilaku Kepatuhan Wajib Pajak Restoran Di Surabaya - Venusita, Lintang; Dyan, Femka (AKRUAL: JURNAL AKUNTANSI, 2013)
AbstractTax arrears increased area in Surabaya. One of the biggest delinquent taxes derived from the Restaurant. It is proved that the level of tax compliance is lacking Restaurant. This study examines the behavior of tax compliance by using variable bebas Attiude, Subjective Norms, and Behavioral control. The purpose of this study is to determine how much influence attitudes, subjective norms, and behavioral control toward tax compliance behavior Restaurant taxpayer in Surabaya. The population in this study are all Restaurants taxpayer in Surabaya. The sample used was 94 Taxpayer Restaurant. The data analysis technique used in this study multiple linear regression. Based on the results of the analysis carried out it could be concluded that attitudes, subjective norms and behavioral control significantly positive effect on taxcompliance behavior Restaurant.